Evaluation of a single-use bioartificial liver (BAL) biocartridge consisting of cryopreservable alginate encapsulated liver cell spheroids as a component of HepatiCan™, a novel bioartificial liver device - Erro, Eloy; Brookshaw, Tom; Fuller, Barry; Chandel, Sweta; Mendonca da Silva, Joana; Zotova, Elizaveta; Chalmers, Sherri-Ann; Watt, Alfie; Selden, Clare (Frontiers in Bioengineering and Biotechnology, 2025)
Introductionalternative therapies to complement liver transplantation and treat patients with liver failure are not available. In this study, a clinical scale single-use biocartridge was developed for use as part of a novel Bioartificial Liver device (HepatiCan™), utilising conditioned human-derived alginate encapsulated liver spheroids (AELS), within a fluidised bed.Methodsto develop the optimal biocartridge, two designs (B2 and B3) were created and modelled to best replicate the performance of our preexisting reusable cartridge (B1). The suitability of designs, and their ability to deliver the required hydrodynamic conditions for AELS, during both spheroid production and treatment phases, was addressed by computational fluid dynamics (CFD). Subsequently, the B3 biocartridge was produced and tested under continuous fluidisation conditions for the growth after encapsulation and recovery after cryopreservation of micro-spheroids in hydrogel scaffolds (AELS).Resultsthe main difference between the designs in (B2 and B3) was the base plate flow distributor. Preserving the hole pattern in the base plate, between B1 and B3, was critical for mimicking fluid flow. Additionally, increasing the number of orifices in the cross-patterned base plate design (B3) provided further benefits: maintaining homogeneity in fluid velocity distribution, whilst avoiding “dead-flow” zones. During AELS culture (using B3 format), a cell density of 24.27 ± 3.0 × 106 cells/mL of beads was achieved by day 11. Additionally, post-thaw recovery (PTR) culture of previously cryopreserved clinical doses of AELS was performed for up to 4 days. Return to the pre-freeze total biomass (6.34 ± 0.9 × 1010 cells of AELS) was achieved after 3 days of PTR; AELS growth continued to a total biomass of 8.48 ± 1.6 × 1010 cells by 4 days.Discussionthe final biocartridge design (B3) was as effective in fluid distribution as the original (B1). B3 surpassed B1 in velocity uniformity over the first 10 mm above the base plate, critical for good mass transfer between biomass and perfusing fluid in the fluidised bed. Sustained biological function for AELS after PTR was demonstrated. One remarkable advantage of this biocartridge is the recovery of functional AELS biomass after cryopreservation. Thus, we facilitate the off-the-shelf availability, whilst preserving essential biological functionality.